2018
DOI: 10.1111/jan.13797
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in women who have experienced intimate partner violence

Abstract: The alarming rate of obesity among abused women suggests that these women are at great risk for obesity, which necessitates clinical consideration. The study findings highlight the need to treat depressive symptoms to manage and prevent obesity among IPV and child abuse survivors. Specifically, nurses should tailor interventions that address mental health outcomes of abuse in managing obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 97 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…Possible explanations for the relationship between spousal violence victimization and nutritional deficiencies may include the withholding of food and a mediating effect of psychological distress that could trigger weight loss [33,34]. While previous studies in western countries and in Saudi Arabia [19,20,21,22] found that having experienced intimate partner violence among women increased the odds for obesity, this study found that lifetime spousal physical and/or sexual violence victimization among women decreased the odds of being overweight or obese. This possible cultural difference needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for the relationship between spousal violence victimization and nutritional deficiencies may include the withholding of food and a mediating effect of psychological distress that could trigger weight loss [33,34]. While previous studies in western countries and in Saudi Arabia [19,20,21,22] found that having experienced intimate partner violence among women increased the odds for obesity, this study found that lifetime spousal physical and/or sexual violence victimization among women decreased the odds of being overweight or obese. This possible cultural difference needs further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Other health risks, such as low body mass index (BMI) [11,18] and obesity [19,20,21,22], were found at a higher rate in women who had experienced lifetime intimate partner violence compared to women who had never experienced intimate partner violence. A number of studies found that intimate partner violence victimization was associated with various health compromising behaviours, such as tobacco use [7,13,21,22,23,24], (heavy) alcohol use [7,22,23,24], eating unhealthy foods [25], and termination of pregnancy [26].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies on exposure to IPV and the association with adverse health outcomes would be better suited for causal interpretation, although the currently available survey data already provide some convincing insights into the problem under investigation. Second, it has been shown that exposure to violence during childhood may increase subsequent exposures at adulthood [77,97,98], which may lead to excess weight. However, the study lacks data on violence experienced during childhood.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The details of each study are presented in Table 1. Some studies used the same data set but were published as separate papers (Alhalal, 2016(Alhalal, , 2018Eldoseri & Sharps, 2017;Eldoseri et al, 2014); thus, these studies were counted as one. The reviewed studies were published between 2002 and 2017.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%